Application of Market Basket Analysis to Optimize Marketing Strategies in MSMEs Diah Cookies - Oksana Khoirunnida; Ghea Sekar Palupi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
MSMEs Diah Cookies are micro businesses in the culinary sector that produce various types of pastries and other preparations. Even though it has daily sales transaction data, the use of this data in analyzing consumer behavior is still not optimal. This study aims to identify consumer purchasing patterns using Market Basket Analysis with Apriori algorithm. and designing a marketing strategy based on daily sales transaction data for the January-November 2024 period. The data is processed using RapidMiner Studio software. The results of the study showed that there was a pattern of buying products that were often purchased at the same time, such as the combination of Nastar Cheese and Sago Cheese associated with Kastangel Ori, Choco Rollcake with Cheese Rollcake, and Akuroti variant of Choco Chunk and Tiramisu associated with Oreo Cream Cheese. These patterns are used as the basis for the preparation of marketing strategies, such as product bundling, store layout arrangements, and product arrangement in storefronts (planograms). Based on the results of the study, the application of Market Basket Analysis has proven to be effective in providing relevant insights to support marketing strategy decision-making in Diah Cookies MSMEs.